Development of a novel porous scaffold: assessment of its suitability for cardiac muscle engineering - Hidalgo-Bastida, Lilia Araida (2008)
Cellular transplantation, a current therapy for cardiac failure, does not consider the need for a physical support or biochemical factors required by the cardiomyocyte. The aim of this project was to establish the Extra Cellular Matrix (ECM), architectural and mechanical properties of a flexible scaffold to assist the maintenance of a cardiac cell line cultured under mechanical stimuli. Previously, mechanical stimulation has been proved to have an effect in cardiomyocytes similar to that of growth factors on other cells and promotes protein expression, differentiation and survival [1]. Poly-(1,8-octanediol-co-citric acid) [POC] is an elastomer that can be processed into scaffolds for tissue engineering. Mechanical properties of the POC were compared at different porosity, storage method and strain rate. POC, with an ultimate elongation of 60-160%, did support cardiac cell attachment when coated with fibronectin. Seeding strategies were evaluated to find optimal conditions and static seeding resulted more favourable for cell adhesion and survival than other dynamics approaches. In collaboration with the University of Leeds, cardiomyocytes were cultured in a dynamic bioreactor, Tencell, under continuous and discontinuous stretching regimes. Mechano-stimulation of cardiac constructs encouraged cell survival in the discontinuous regime and up-regulated the expression of actc1 and nppa genes regardless of the treatments. It was concluded that although mechanical stimulation had a positive effect on cell survival and gene expression, tissue formation was not promoted.